Duodenal Obstruction as First Presentation of Metastatic Breast Cancer - Sami Khairy; Ayman Azzam; Shamayel Mohammed; Kausar Suleman; Abdurahman Khawaji; Tarek Amin (Case Reports in Surgery)
The metastatic breast cancer to the duodenum is rare in spite of common breast cancer. In this paper, we are reporting a rare case of 50-year-old lady who presented with intestinal obstruction as result of metastatic breast cancer which completely responds to chemotherapy. The tumor presents again as brain metastasis after stop of Herceptin due to cardiac toxicity.